Introduction of an electronic monitoring system for monitoring compliance with Moments 1 and 4 of the WHO "My 5 Moments for Hand Hygiene" methodology - Cheng, Vincent CC; Tai, Josepha WM; Ho, Sara KY; Chan, Jasper FW; Hung, Kwan Ngai; Ho, Pak Leung; Yuen, Kwok Yung (BMC infectious diseases, 2011)
MedSense is an electronic hand hygiene compliance monitoring system that provides Infection Control Practitioners with continuous access to hand hygiene compliance information by monitoring Moments 1 and 4 of the WHO "My 5 Moments for Hand Hygiene" guidelines. Unlike previous electronic monitoring systems, MedSense operates in open cubicles with multiple beds and does not disrupt existing workflows. This study was conducted in a 6-bed neurosurgical intensive care unit with technical development and evaluation phases. Healthcare workers (HCWs) wore an electronic device in the style of an identity badge to detect hand hygiene opportunities and compliance. We compared the compliance determined by the system and an infection control nurse. At the same time, the system assessed compliance by time of day, day of week, work shift, professional category of HCWs, and individual subject, while the workload of HCWs was monitored by measuring the amount of time they spent in patient zones. During the three-month evaluation phase, the system identified 13,694 hand hygiene opportunities from 17 nurses, 3 physiotherapists, and 1 healthcare assistant, resulting in an overall compliance of 35.1% for the unit. The per-indication compliance for Moment 1, 4, and simultaneous 1 and 4 were 21.3% (95%CI: 19.0, 23.6), 39.6% (95%CI: 37.3, 41.9), and 49.2% (95%CI: 46.6, 51.8), respectively, and were all statistically significantly different (p < 0.001). In the four 20-minute sessions when hand hygiene was monitored concurrently by the system and infection control nurse, the compliance were 88.9% and 95.6% respectively (p = 0.34), and the activity indices were 11.1 and 12.9 opportunities per hour, respectively. The hours from 12:00 to 14:00 had a notably lower compliance (21.3%, 95%CI: 17.2, 25.3) than nearly three quarters of the other periods of the day (p < 0.001). Nurses who used shared badges had significantly (p < 0.01) lower compliance (23.7%, 95%CI: 17.8, 29.6) than both the registered nurses (36.1%, 95%CI: 34.2, 37.9) and nursing officers (34.0%, 95%CI: 31.1, 36.9) who used named badges. MedSense provides an unobtrusive and objective measurement of hand hygiene compliance. The information is important for staff training by the infection control team and allocation of manpower by hospital administration.